New femoral evidence from the Afar reveal the early evolution of habitual squatting behaviors in the genus Theropithecus - Pallas, Laurent; Nakatsukasa, Masato; Daver, Guillaume; Guy, Franck; Rio, Noam; Rowan, John (Frontiers in Ecology and Evolution, 2025)
IntroductionThe femoral anatomy of fossil Theropithecus is poorly known, although it provides critical data for inferring squatting behaviors, a characteristic trait of extant Theropithecus gelada.MethodsHere, we describe and provide functional and taxonomic interpretations on two subcomplete femora from the Afar Depression using a combination of traditional morphometrics (bivariate and multivariate) and 2D geometric morphometric combined with multivariate analyses and hierarchical clustering. ResultsThe ca. 3.20 Ma A.L. 206–1 femur is identified as the oldest known and most complete femur of an adult Theropithecus cf. oswaldi darti and shows a morphology similar to that of extant T. gelada. It supports the hypothesis of an early emergence of squatting behaviors in Theropithecus, prior to the onset of dental adaptations related to the grazing diet of the genus. The ca. 2.60 Ma A.L. 94–5 femur is identified as the oldest and most complete femur known of an adult Theropithecus cf. oswaldi oswaldi. Its knee anatomy is distinct from that of T. o. darti but it nonetheless shares with T. gelada and other fossil Theropithecus functional traits related to squatting behaviors. Unexpected convergences with arboreal cercopithecids are observed in Theropithecus brumpti, indicating diversity in the femoral functional anatomy of Theropithecus. DiscussionOverall, our study highlights the future need to link femoral anatomical diversity with postural and locomotor behaviors by combining paleontological data with neontological data including biomechanical data on the squatting and climbing of large extant papionins.